Theorizing the dynamics of social processes - Dahms, Harry F.; Hazelrigg, Lawrence (Current perspectives in social theory ;, 2010)
The chapters in this volume represent steps in the direction of demonstrating the importance of efforts to theorize the dynamics of specific social, cultural, political, and/or economic processes to the social sciences in general. They aim to clarify how those efforts are central to the core mission of each of the social sciences, and how social theory is both especially well positioned to tackle this challenge and to accept responsibility for illuminating related possibilities. Papers address the nature and importance of "process" in studying modern (industrialized, post-industrial, capitalist, postmodern, globalizing, etc.) societies at macro, meso, or micro-scale. The volumes overall purpose is to assemble a set of essays that invent, develop, and/or demonstrate strategies for theorizing one or several dynamic processes, so as to identify, illustrate by example, and analyze specific problems as well as connect theorizations of process across different disciplines of inquiry.